(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The engine can be converted in to Low Heat rejection engine by applying ceramic based materials because of their good thermal properties. Ceramic materials are generally amorphous as well as crystalline in structure, which will affect the combustion process, leads to better performance and decreases exhaust emissions of the engine. Ceramic coatings show significant reduction in abrasion failure and wear of reciprocating parts of the engine. They are having very good application in the fields of IC engine as thermal barrier coating to improve engine efficiency by decreasing exhaust emissions, energy loss and cooling requirements. As there are numerous research reports are available on the performance of IC engine provided with ceramic coated combustion chamber, but they are majorly discussing about theoretical benefits. Very limited literature is available which explains the practical scenario of engine provided along insulated chambers of combustion. Because success have been reported from the engine along chamber combustion which is ceramic coated, ceramic components are also developed which are using as a part of the engine and are in service mainly for reduction of heat loss from combustion chamber walls. Apart from this many researchers are also noticed failures and drop in execution of engine provided along ceramic coated combustion chamber.